1990
DOI: 10.1177/1532673x8001800203
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects On State Governors

Abstract: A large body of research on the impact of economic conditions on elections has been amassed. Past research emphasized congressional and presidential elections. The present research extended the question of economic effects to the state level. Are governors held responsible for the economic conditions of their states? The existing studies at the state level all used aggregate data and concluded that states' economies do not affect the fortunes of the governors. The studies inferred that the national economy, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 8 publications
0
49
1
Order By: Relevance
“…Chubb's (1988) conclusion that state politicians do not suffer at the polls for state economic conditions is consistent with this, although some of Chubb's results suggest that state economic conditions affect state legislative seat changes. Howell and Vanderleeuw (1990) have demonstrated that state economic conditions do affect gubernatorial approval ratings. In short, evidence of economic voting in state elections in response to state economic conditions is somewhat mixed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Chubb's (1988) conclusion that state politicians do not suffer at the polls for state economic conditions is consistent with this, although some of Chubb's results suggest that state economic conditions affect state legislative seat changes. Howell and Vanderleeuw (1990) have demonstrated that state economic conditions do affect gubernatorial approval ratings. In short, evidence of economic voting in state elections in response to state economic conditions is somewhat mixed.…”
mentioning
confidence: 98%
“…Until recently, however, economic voting in state elections has received less emphasis. Although economic voting in state elections has become the subject of several studies (Peltzman 1987;Chubb 1988;Howell and Vanderleeuw 1990), virtu-ally no attention has been given to the question of how economic conditions might affect support for state ballot propositions. This is unfortunate, given the prominence of ballot propositions in many American states (Magleby 1984).…”
mentioning
confidence: 99%
“…have a significant [albeit small] impact on gubernatorial election outcomes. "3 More recently, using survey data, Stein (1990), Howell and Vanderleeuw (1990), and Atkeson and Partin (1995) all found substantial effects of the state economic evaluations on gubernatorial voting.4 In short, 'In 1982, when voters were asked "Who is to blame for the state's economic problems? ", 15% named the governor and 18% named both the president and governor (with 25% picking the president and the remaining respondents saying "neither") (Stein 1990, 41).…”
mentioning
confidence: 99%
“…How well these findings apply to governor approval is somewhat controversial. Some studies show that state unemployment affects a governor's popularity (Leyden and Borrelli 1993;Hansen 1999;Crew et al 2002;Howell and Vanderleeuw 1990;Orth 2001), while others claim that governors have less to fear from their state economies (Chubb 1988;Peltzman 1987).…”
Section: Pillars Of Approvalmentioning
confidence: 97%